Kepastian Hukum dan Perlindungan Hak Istri Atas Gugurnya Izin Ikrar Talak Setelah 6 Bulan (Studi Kasus Perkara No. 274/Pdt.G/2023/Pa.Pyb) - Siti Aminah; Muhamad Hasan Sebyar; M. Fadhlan Is (Universitas Pangeran Diponegoro Nganjuk, 2026)
This study aims to analyze the legal certainty and protection of a wife's rights regarding the expiration of the talak (divorce) pronouncement permit after six months, and to examine legal measures or frameworks to prevent the abuse of the right to divorce by the husband in religious court practices. The study employs a normative-juridical method utilizing case, statute, and conceptual approaches. Data collection was conducted through library research using primary, secondary, and tertiary legal materials, followed by qualitative analysis using a descriptive-analytical approach that correlates legal norms (das sollen) with empirical realities (das sein). The findings indicate that the provision regarding the expiration of the talak pronouncement permit after six months provides formal and procedural legal certainty for both parties husband and wife. However, in practice, the protection of the wife's rights remains merely normative and fails to fully guarantee substantive justice, particularly when the husband neglects obligations such as providing maintenance (nafkah). This situation creates an imbalance in legal standing and opens the door for the husband to abuse the right to divorce. Therefore, more responsive legal measures and frameworks are required, including strengthening the role of judges, imposing sanctions for the abuse of rights, optimizing mediation, and reforming regulations to prioritize the protection of women's rights. The Maqashid Sharia (objectives of Islamic law) approach also serves as a crucial foundation for ensuring that divorce practices align with principles of justice, public interest (maslahah), and the protection of vulnerable parties